Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00276-014-1405-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of female pelvic cavity for nerve sparing radical hysterectomy

Abstract: The deep uterine vein is suggested as an anatomical landmark during surgery, to process the CL and preserve the pelvic splanchnic nerves. The middle and inferior vesical veins can be used as the landmark to preserve the vesical branch of the IHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The last columns depict the identifiability and level of agreement with positional references, anatomist, and radiologistNerve/ plexusRecords included in quantitative synthesisMain positional referenceIdentifiability (%) a Conform positional reference (%) b Level of agreement anatomist (Likert score 2)Level of agreement radiologist (Likert score 2)Lumbosacral plexusNANA20 (100)NA20 (100)20 (100)Sacral nervesNANA20 (100)NA20 (100)20 (100)Obturator nerve2 [11, 12]Appearance lateral to confluence of the internal and external iliac vein20 (100)20 (100)20 (100)20 (100)Sympathetic trunk4 [1316]Entrance pelvis from either side of the lumbar spine dorsal from common iliac vein to course medial to sacral foramina19 (95)19 (100)19 (100)19 (100)Superior hypogastric plexus12 [7, 1626]Division at or just below the level of the sacral promontory14 (70)14 (100)14 (100)14 (100)Hypogastric nerve12 [7, 16, 19, 21, 2532]Course just medial to internal iliac vessels16 (80)16 (100)16 (100)16 (100)Inferior hypogastric plexus17 [7, 16, 21, 2538]Ureter crosses, just before entering the bladder, anterior to the IHP…”
Section: Resultsmentioning
confidence: 99%
“…The last columns depict the identifiability and level of agreement with positional references, anatomist, and radiologistNerve/ plexusRecords included in quantitative synthesisMain positional referenceIdentifiability (%) a Conform positional reference (%) b Level of agreement anatomist (Likert score 2)Level of agreement radiologist (Likert score 2)Lumbosacral plexusNANA20 (100)NA20 (100)20 (100)Sacral nervesNANA20 (100)NA20 (100)20 (100)Obturator nerve2 [11, 12]Appearance lateral to confluence of the internal and external iliac vein20 (100)20 (100)20 (100)20 (100)Sympathetic trunk4 [1316]Entrance pelvis from either side of the lumbar spine dorsal from common iliac vein to course medial to sacral foramina19 (95)19 (100)19 (100)19 (100)Superior hypogastric plexus12 [7, 1626]Division at or just below the level of the sacral promontory14 (70)14 (100)14 (100)14 (100)Hypogastric nerve12 [7, 16, 19, 21, 2532]Course just medial to internal iliac vessels16 (80)16 (100)16 (100)16 (100)Inferior hypogastric plexus17 [7, 16, 21, 2538]Ureter crosses, just before entering the bladder, anterior to the IHP…”
Section: Resultsmentioning
confidence: 99%
“…The deep UV is said to be more robust and the principal functional component of the uterine venous drainage. 24 Li et al reported up to six tributaries forming the deep UV 25 ; three branches were reported the most common number of tributaries of the deep UV (63.3%; n = 15). 25 The UV joins the IIV at various locations and in various numbers, that is, occasionally as multiple vessels.…”
Section: Uterine Veinmentioning
confidence: 98%
“…24 Li et al reported up to six tributaries forming the deep UV 25 ; three branches were reported the most common number of tributaries of the deep UV (63.3%; n = 15). 25 The UV joins the IIV at various locations and in various numbers, that is, occasionally as multiple vessels. During the retrieval of the uterus from an LD, multiple UV may pose a technical difficulty because the UV may be located both ventrally and dorsally to the ureter.…”
Section: Uterine Veinmentioning
confidence: 98%
See 2 more Smart Citations